تحليل الأثر المتبقي من بعض المبيدات الكلورية العضوية في مياه الشرب - يوسف عبد اللطيف (Latakia University Journal -Basic Sciences Series, 2018)
قمنا بتحليل عدد من عينات مياه الشرب للكشف الكمي عن تراكيز بعض المركبات الكلورية العضوية الموجودة بتقنية الكروماتوغرافيا الغازية وكاشف التقاط الإلكترون ((ECD-63Ni وذلك بعد استخلاص هذه المركبات من عينات المياه بطريقتين الأولى هي: استخلاص سائل/سائل والأخرى هي استخلاص الطور الصلب (SPE)، وبمقارنة طريقتي الاستخلاص موضوع هذا البحث تبين لنا أن الطريقة (SPE) هي الأنسب لعدة أسباب أهمها أن حجم العينة أقل، وكان الزمن اللازم لتحضير العينة وكمية المحلات المستخدمة أقل بكثير من الطريقة الأولى بالإضافة إلى ذلك دقة النتائج العالية التي يمكن الاعتماد عليها. هذا ما سنوضحه في بحثنا هذا. We have analyzed a number of drinking water samples to determine quantitatively the concentration of some organochlorine compounds in water samples, using gas chromatography (G.C) equipped with Electron-Capture detecto 63Ni. The G.C analysis was performed after extracting the water samples by two methods: the first one, was by Liquid/Liquid Extraction, and the second one was by solid Phase Extraction (SPE). comparing these two extraction methods, we found out that the SPE is in this case was more appropriate than the Liquid/Liquid extraction for the following reasons: it needs smaller size, less time to prepare the sample, less volume of used solvents, and high accuracy.